Neuronal mTOR Outposts: Implications for Translation, Signaling, and Plasticity - Altas, Bekir; Romanowski, Andrea J.; Bunce, Garrett W.; Poulopoulos, Alexandros (Frontiers in Cellular Neuroscience, 2022)
The kinase mTOR is a signaling hub for pathways that regulate cellular growth. In neurons, the subcellular localization of mTOR takes on increased significance. Here, we review findings on the localization of mTOR in axons and offer a perspective on how these may impact our understanding of nervous system development, function, and disease. We propose a model where mTOR accumulates in local foci we term mTOR outposts, which can be found in processes distant from a neuron's cell body. In this model, pathways that funnel through mTOR are gated by local outposts to spatially select and amplify local signaling. The presence or absence of mTOR outposts in a segment of axon or dendrite may determine whether regional mTOR-dependent signals, such as nutrient and growth factor signaling, register toward neuron-wide responses. In this perspective, we present the emerging evidence for mTOR outposts in neurons, their putative roles as spatial gatekeepers of signaling inputs, and the implications of the mTOR outpost model for neuronal protein synthesis, signal transduction, and synaptic plasticity.